Pengaruh Harga dan Promosi terhadap Minat Beli Konsumen: Studi Kasus pada Ayam Hisana Rajawali Medan - Mhd Reyhan Abdillah (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
The aim of this research is to determine and analyze the influence of Price and Promotion on Consumer Interest (Case Study at Hisana Fried Chicken Rajawali Medan. The research method used is exploratory research, where variables are measured using a Likert scale. Data collection methods are carried out by (interviews), with a list of questions (questionnaires) and documentation studies. The population in this study is all consumers on HFC Jalan Rajawali Medan.. totaling 100 people. Sample collection was carried out using the saturated sampling method or better known as census. In this study, the population was relatively small, namely 100 people. Data processing used SPSS version 23 software, with descriptive analysis and multiple regression hypothesis testing; (3) simultaneously there is a positive and significant influence between experimental marketing variables and customer satisfaction on experimental marketing and customer satisfaction on repurchase interest in HFC Jalan Rajawali Medan.